Green feed increases antioxidant and antineoplastic activity of buffalo milk: A globally significant livestock. (15th May 2021) - Salzano, Angela; Neglia, Gianluca; D'Onofrio, Nunzia; Balestrieri, Maria Luisa; Limone, Antonio; Cotticelli, Alessio; Marrone, Raffaele; Anastasio, Aniello; D'Occhio, Michael J.; Campanile, Giuseppe
Highlights: Green feed increases concentration of health-promoting molecules in buffalo milk. Green feed increases the antioxidant activity of buffalo milk. Green feed increases the antineoplastic of buffalo milk. Increased biomolecules support buffalo milk consumption within a balanced diet. Abstract: The effect of green feed on health-promoting biomolecules in milk was examined in dairy buffaloes. Buffaloes received a total mixed ration (TMR) (Control, C; n = 40) or TMR + alfalfa green feed (30% of diet) (Treated, T; n = 40). Biomolecules and functional activity were measured in milk obtained twice-monthly. Treated buffaloes had higher milk l -carnitine, acetyl-l -carnitine, propionyl-l -carnitine and δ-valerobetaine (P < 0.01). They also had higher antioxidant activity (P < 0.01). Compared with C buffaloes, milk of T buffaloes improved the viability of endothelial cells exposed to high-glucose (P < 0.01), and reduced intracellular lipid peroxidation, reactive oxygen species (ROS), and cytokine release (P < 0.01). Milk of T buffaloes inhibited with greater potency the viability of human HCT116 and Cal 27 cancer cells (P < 0.001). The findings show that including green feed in the diet of dairy buffaloes enhances health-promoting biomolecules and the antioxidant and antineoplastic properties of milk.